Anti-inflammatory effects of siponimod on astrocytes. (November 2022) - Ogasawara, Akihiro; Takeuchi, Hideyuki; Komiya, Hiroyasu; Ogawa, Yuki; Nishimura, Koki; Kubota, Shun; Hashiguchi, Shunta; Takahashi, Keita; Kunii, Misako; Tanaka, Kenichi; Tada, Mikiko; Doi, Hiroshi; et al.
Abstract: Siponimod, which is approved to treat active secondary progressive multiple sclerosis, acts as a functional antagonist of sphingosine-1-phosphate (S1P) receptor 1 (S1P1 ) and an agonist of S1P5 . S1P1 antagonization, which inhibits lymphocyte egress from lymphoid tissues and subsequent infiltration into the central nervous system (CNS), is considered the main therapeutic mechanism of siponimod. In addition, siponimod's direct effects on CNS glial cells are another potential neuroprotective mechanism because siponimod can penetrate the blood–brain barrier and CNS glial cells express S1P receptors. However, it remains uncertain whether siponimod directly affects CNS glial cells. In this study, we investigated siponimod's effects on astrocytes using mouse primary cultures. Siponimod suppressed nuclear factor kappa B activation and pro-inflammatory cytokine production. Using antagonists for S1P1 and S1P5, we found that siponimod partially exerts its anti-inflammatory effects via S1P1, but not via S1P5 . Moreover, siponimod also inhibited histone deacetylase, suggesting that siponimod exerts broad anti-inflammatory effects via S1P1 antagonization and histone deacetylase inhibition. Siponimod might suppress disease progression in multiple sclerosis in part via direct inhibition of astroglial CNS neuroinflammation. Graphical Abstract: ga1 Highlights: Siponimod has anti-inflammatory effects on astrocytes via S1P1 antagonization. Siponimod also inhibits astroglial HDAC activity. S1P1 antagonization and HDAC inhibition might contribute to siponimod's effects.